Dynamical Analysis of a Vehicle to Trailer Connection during Braking - Avramov, Nikola (Springer Science and Business Media LLC, 2022)
In this paper the dynamical analysis of a vehicle to trailer connection during braking is presented. At first both the vehicles, motor vehicle and trailer are analysed as a separate vehicles, driving with same starting velocity and same braking force applied but no connection between them. Than the dynamic analysis is conducted for two types of connection, one rigid and second one with inertial brake between. The chronology of the study is to find the displacement of the vehicles as separate systems and to conduct the dynamic analysis of the two connections as a difference in the travel till zero velocity. The aim of the paper is to acknowledge the stiffness of the vehicle to trailer connection during braking
Keywords: Dynamic analysis, Inertial brake, Motor vehicle, Rigid connection, Trailer